A Study on the Fresh Water Fish Diversity of Mora Dhansiri River, Assam, India - Saha , Alo; Ahmed , Shehenuwaz; Das , Rajdeep; Bhattacharjee , Swarupa; Kashyap , Sudha Chandan; Bhattacharjee , Chinmoyee; Sur , Somoyita (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The Mora Dhansiri River, situated in Darrang District, Assam, India, harbors a diverse array of freshwater fish species, contributing significantly to the region's biodiversity. Through comprehensive sampling efforts, this study identified a total of 29 fish species across 05 orders and 12 families. Cypriniformes dominated the catch list with 17 species, followed by Perciformes with 04 species, Siluriformes with 05 species, Synbranchiformes with 02 species, and one species from Gobiiformes. The most abundant family was Cyprinidae, comprising 22 species, followed by Bagridae and Cobitidae with four species each. The study revealed prominent genera such as Labeo, Puntius, Mystus, and Channa, with multiple species representing each genus. Notably, the presence of exotic species such as Cyprinus carpio, Ctenopharyngodon idella, and Hypophthalmichthys molitrix underscores the influence of adjacent private ponds on the river's fish diversity. Of the recorded species, 19 were deemed edible and suitable for aquarium trade, with three species also possessing medicinal value. Furthermore, the study assessed the conservation status of the fish species, revealing that 2.19% were endangered, 4.54% vulnerable, and 6.81% near-threatened, while 77.2% were categorized as least concern. Additionally, 2.27% of species were classified as data deficient, and 9.09% were not accessed. The presence of near-threatened species like Hypophthalmichthys molitrix highlights the conservation significance of the Mora Dhansiri River. However, anthropogenic pressures such as industrial effluents, pesticide use, overexploitation, and habitat destruction pose significant threats to the river's aquatic biodiversity. Urgent conservation measures are needed to safeguard these valuable resources and ensure their sustainable management for future generations.